Heart Failure (HF): Recent innovations in clinical therapy and critical profiles of acute and chronic forms - Giulio Perrotta (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Background and objectives: Heart failure is a pathological condition characterized by the inability of the heart to pump (cardiac output) an adequate amount of blood to meet the metabolic needs of the body or, at any rate, to be able to do so only at the expense of increased filling pressures in one or more cardiac chambers and the upstream venous circulation. The research group states here the primary objective of expanding the indications contained in the ESC 2021 with the results of the last year on the subject of treatment profiles, to facilitate a better understanding of the overall clinical picture and contribute to the next edition of the guidelines. Materials and methods: Systematic literature review in the English language from January 1, 2021, to September 30, 2022, on PubMed/MedLine, Web on Science, and Cochrane archive. Our search strategy retrieved 8,317 articles. We excluded books and papers, meta-analyses, reviews, and systematic reviews and selected only 46 studies most significant about the clinical trial and randomized controlled trial. Results: The recent ESC 2021 guidelines are accurate and timely, and have confirmed their usefulness from a functional perspective, including concerning certain aspects that were represented as a "grey area". Early risk prediction plays a key role in the subsequent management of patients, and to optimize risk prediction and intensity of management, one should take into account that: a) biomarkers have improved the understanding of the pathophysiology of heart failure and may therefore help to adjust the intensity of management in AHF; b) among the wide variety of biomarkers currently available, NT-proBNP and cTn seem the most promising in this indication; c) among the risk scores described, those combining demographic and clinical parameters with biomarkers in a model with routinely available rapid variables seem the most promising tools; d) in addition to biomarkers, age, systolic blood pressure, respiratory rate, oxygen saturation, creatinine, electrolytes, and blood urea nitrogen are the most commonly used predictor variables in the risk scores described; e) among the models selected, the MEESSI-AHF risk score appears to be currently the most promising tool for predicting the risk of AHF; f) during the management of decompensated patients (and in later stages), the psychological aspect is completely ignored, thus promoting the worsening of psychological symptoms (the need is as evident during the acute episode as it is in the daily management of chronic heart failure).  Conclusions: The scientific literature search enriched the structure of ESC 2021, suggesting its implementation, with other findings related to new drug therapies such as Sotagliflozin, Hydrochlorothiazide Apabetalone, Alprostadil, Empagliflozin, Sacubitril/Valsartan, Dapagliflozin, Sodium-glucose co-transporter-2 inhibitors, and biomarkers such as Urinary sodium (UNa+), IL-6 levels and rh-brain natriuretic peptide (rhBNP), as well as the use of mindful breathing session, osteopathic manipulative treatment, electrical muscle stimulation, low-level tragus stimulation, venoarterial extracorporeal membrane oxygenation, oral nutritional supplements, and the correlative hypothesis between heart failure and intestinal dysbiosis, also concerning the psychological profile. However, these clinical studies suffer from some limitations that will necessarily have to be taken into account, such as the limited size of the population sample selected or the conflict of interest determined by the fact that some research is funded by the same pharmaceutical company producing the drug used that do not necessarily represent a negative limitation on the results obtained from studies.